2015
DOI: 10.18765/jes.v30i1.6016
|View full text |Cite
|
Sign up to set email alerts
|

Training Needs of Agricultural Extension Workers in Senegal

Abstract: Agricultural extension in Senegal is critical to increasing agricultural production among the nation's smallholder farmers who make up 60 percent of the country's 14 million population. The paper argues that whereas the Government has recognized the importance of an integrated rural development approach to holistic development and urges extension workers to become development facilitators it fails to recognize the importance of providing these agents with training in development and communication, otherwise kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…However, in the case of Indonesia, the government framed it as a law. A majority of respondents also agreed that smallholder farmers could not pay for extension, which is in line with studies carried out in many African countries (Agunga, Ndiaye, and Igodan 2014). A significant finding also was that for effective coordination of activities across sectors, the extension system must be located in a neutral location outside the Ministry of Agriculture.…”
Section: Challenges In Implementing the New Extension Systemsupporting
confidence: 78%
“…However, in the case of Indonesia, the government framed it as a law. A majority of respondents also agreed that smallholder farmers could not pay for extension, which is in line with studies carried out in many African countries (Agunga, Ndiaye, and Igodan 2014). A significant finding also was that for effective coordination of activities across sectors, the extension system must be located in a neutral location outside the Ministry of Agriculture.…”
Section: Challenges In Implementing the New Extension Systemsupporting
confidence: 78%
“…Many studies have found that growers emphasize learning from their own experiences and those of other farmers rather than Extension agents and scientific research, which are often viewed as grounded in conventional management approaches (Eckert and Bell, 2005; Agunga and Igodan, 2007; Middendorf, 2007; Parker and Lillard, 2013; Jabbour et al ., 2014; Crawford et al ., 2015; Marabesi et al ., 2021). Growers responding to our surveys also placed less emphasis on Extension resources as compared to other knowledge and training opportunities regarding the development of their disease management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…A thorough body of literature underscores how the lack of understanding and recognition of these complexities have created an unstable bridge between the Extension and outreach offered by land grant universities and organic growers' needs (Beus and Dunlap, 1992; Agunga and Igodan, 2007; Middendorf, 2007; Sarker and Itohara, 2009; Crawford et al ., 2015; Marabesi and Kelsey, 2019; Marabesi et al ., 2021). Strategies that could result in more effective outreach programming regarding organic production practices include the identification of the intersection of stakeholder interests with practice outcomes (e.g.…”
Section: Introductionmentioning
confidence: 99%